The roles of hajj and umrah facilitating guides in promoting healthy lifestyles among Indonesian pilgrims - Iwan Yulis Setiawan; Supriyati Supriyati; Probosuseno Probosuseno (Berita Kedokteran Masyarakat (BKM), 2020)
Background: Hajj pilgrimage has the potential to spread acute and rapid infectious respiratory and digestive diseases because of the gathering of over two million people from various countries with different characteristics. Purpose: This study explored the role of KBIHU in promoting the healthy behavior of prospective pilgrims in the Cilacap Regency.Method: Qualitative methods with a case study approach. Data analysis uses the thematic analysis of Miles and Huberman's interactive model. Results: The results showed five themes, six categories, and twenty-five subcategories. 1]. Internal management roles in promoting healthy behavior: (a) institutional perception of authority and its limitation, and networking, (b) guidance, service, assistance, and protection functions, and (c) planning, implementation, and evaluation. 2]. Efforts to promote healthy behavior:  coordination between agencies, coordination with the public health office and community health center, and the role of innovation. 3]. tips on promoting healthy behaviors: maximizing the role of mentors, involving pilgrims and alumni of health workers, involving fellow worshipers, use of social media, AKHI, TKHI, and "karu-karom." 4]. KBIHU support: health policy, the pilgrimage "istithaah," and pilgrims' rights and obligations. 5]. Problems in implementation: the fact of pilgrims and pilgrimage diseases.